GOUT CLASSIFICATION CRITERIA (ACR/EULAR GUIDELINES) - M. S. Eliseev (Научно-практическая ревматология, 2016)
The paper considers the new gout classification criteria approved by the Board of Directors of the American College of Rheumatology (ACR) and the Executive Committee of the European League Against Rheumatism (EULAR). The criteria have been elaborated on the basis of quantitative assessment of the data obtained during the examinations of patients and have high sensitivity (92%) and specificity (89%). These classification criteria will be able to standardize an approach to making up relatively homogeneous groups of patients having the clinical signs of gout to be enrolled into the investigation.